The use of hebel in Ecclesiastes: A political and economic reading - Biwul, Joel K. T. (HTS teologiese studies, 2017)
A hermeneutical cloud still dominates ongoing discourse on the meaning and application of הֶבֶל (hebel), a crucial weaving thread in the book of Ecclesiastes. The Hebrew Qoheleth, presumably the disguised author, proposes the theological ideology of hebel as the totality of human existence in this book. What does Qohelethintend to achieve by asserting and dismissing everything in human experience as hebel (vanity, meaningless, worthless, not beneficial, absurd and enigma)? This article proposes a political and economic reading of Ecclesiastes, holding that the author, from personal observation, saw and addressed life from the point of view of ivory tower aristocrats who sought to control their environment by every means to their benefit. It suggests that a political and economic reading of Ecclesiastes locates another perspective on Qoheleth’s purposes for the use of hebel. As such, it argues that the Qoheleth uses hebel as a literary rhetorical device as an evaluative grid to critique and indict the negative behaviour of the politically powerful and the wealthy, to caution against the reckless abuse of political and economic power to their benefit by those who live in privilege in society, and lastly to give counsel for an appropriate application of such privileged power for the good of society vis-à-vis the transitory, transient and unpredictable nature of human existence.